The Pengaruh Model Pembelajaran Cups Berbasis TPACK terhadap Hasil Belajar Kognitif dan Literasi Digital - Oktaviana, Catur; Dewi, Novi Ratna (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2023)
21st century learning emphasizes the integration of technology and communication (ICT) in teaching and learning activities. The use of ICT is able to support the learning process. Based on the results of interviews at SMPN 1 Pucakwangi, cognitive learning outcomes were still low due to the use of inappropriate learning models and students' lack of understanding of the subject matter. In addition, students' digital literacy is still low due to the lack of application of technology in learning activities. This study aims to analyze students' cognitive abilities and digital literacy using the TPACK-based CUPs learning model. This research method is a quasy experiment using the pretest-posttest control group design method. The results showed that the gain in the experimental class was higher than the control class by 0.712. The results of the effect test using the Independent Sample t-test found a significant difference after treatment with t count > t table of 2.2103 which indicates that there is an effect of using the TPACK-based CUPs learning model on cognitive learning outcomes. Questionnaire data experienced an increase in the average value of digital literacy in the experimental class 81.02, which was greater than the control class. The results of the influence test on the second hypothesis obtained a t count > t table of 2.00452 so that there was a significant difference after treatment.